2019
DOI: 10.1021/acs.jafc.9b05162
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Dose Genistein on the Hypothalamic RNA Profile and Intestinal Health of Female Chicks

Abstract: Genistein is abundant in animal feed. In this study, the side effects of high-dose genistein on intestinal health and hypothalamic RNA profile were evaluated. Chicks exposed to high-dose genistein by intraperitoneal injection (416 ± 21, 34.5 ± 2.5) and feed supplementation (308 ± 19, 27.2 ± 2.1) both showed a reduced body weight gain and feed intake in comparison with the control group (261 ± 16, 22.7 ± 1.6, P < 0.01). In comparison with the control (22.4 ± 0.5, 33.3 ± 2.4), serum levels of albumin and total p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…RNA sequencing was carried out as previously reported [ 62 , 63 ]. Cells were grown with DMSO and genistein (50 μM) for 5 h. Total RNA was isolated using the RNeasy Plus Mini Kit, following the manufacturer’s instructions (Qiagen, Germantown, MD, USA).…”
Section: Methodsmentioning
confidence: 99%
“…RNA sequencing was carried out as previously reported [ 62 , 63 ]. Cells were grown with DMSO and genistein (50 μM) for 5 h. Total RNA was isolated using the RNeasy Plus Mini Kit, following the manufacturer’s instructions (Qiagen, Germantown, MD, USA).…”
Section: Methodsmentioning
confidence: 99%
“…However, Wang, Jiang, Zhang, Liang, and Yang (2014) found that a dose of 20 mg/kg isoflavones reduced villus length, muscle thickness and villus height/crypt depth ratio (V/C) of the duodenum, jejunum and ileum of chicken. The reduced villus height was also observed in ileum of female chicks fed with a high‐dose of genistein (400 mg/kg) (Lv et al., 2019). It has been reported that the effects of dietary isoflavones on intestinal morphology were in a dose‐dependent manner in broiler chickens (Kamboh & Zhu, 2014).…”
Section: Discussionmentioning
confidence: 87%
“…The arcuate nucleus (ARC) within the hypothalamus plays a crucial role in sensing the body's overall energy status 14 . The ARC contains various neuron groups related to energy homeostasis, including orexin neuropeptide Y (NPY)/agouti‐related peptide (AgRP) neurons and orexin opiomelanocortin (POMC) neurons 15‐17 . The addition of dietary additives such as non‐nutritive sweeteners may influence the production of these appetite‐regulating neuropeptides, potentially altering animal feed intake.…”
Section: Introductionmentioning
confidence: 99%
“…14 The ARC contains various neuron groups related to energy homeostasis, including orexin neuropeptide Y (NPY)/agoutirelated peptide (AgRP) neurons and orexin opiomelanocortin (POMC) neurons. [15][16][17] The addition of dietary additives such as non-nutritive sweeteners may influence the production of these appetite-regulating neuropeptides, potentially altering animal feed intake. However, the specific effects of non-nutritive sweeteners on the production of ARC-related appetite-related neurons in the hypothalamus remain unknown.…”
Section: Introductionmentioning
confidence: 99%